Co-parenting and Sexual Partner Concurrency among White, Black, and Hispanic Men in the United States - Taylor, Eboni M. (Sex Transm Dis, 2011)
BACKGROUND: Concurrent sexual partnerships (partnerships that overlap in time) increase the spread of infection through a network. Different patterns of concurrent partnerships may be associated with varying STI risk depending on the partnership type (primary vs. non-primary) and the likelihood of condom use with each concurrent partner. We sought to evaluate co-parenting concurrency, overlapping partnerships in which at least one concurrent partner is a co-parent with the respondent, which may promote the spread of sexually transmitted infections (STIs). METHODS: We examined sexual partnership dates and fertility history of 4928 male respondents in the 2002 National Survey of Family Growth. We calculated co-parenting concurrency prevalence and examined correlates using Poisson regression. RESULTS: Among men with ≥1 pair of concurrent partnerships, 18% involved a co-parent. 33% of black men involved in co-parenting concurrency were < 25 years, compared to 23% of Hispanics and 6% of whites. Young black men (age 15–24) were more likely to engage in co-parenting concurrency than white men, adjusting for socio-demographic characteristics, sexual and other high-risk behaviors, and relationship quality. Compared to white men age 15–24, black and Hispanic men were 4.60 (95% CI 1.10, 19.25) and 3.45 (95% CI 0.64, 18.43) times as likely to engage in co-parenting concurrency. CONCLUSION: Almost one in five men engaging in concurrent sexual partnerships in the past year was a co-parent with at least one of the concurrent partners. Understanding the context in which different types of concurrency occur will provide a foundation on which to develop interventions to prevent STIs.